ICLLIC PROMOTES GREATER GLOBAL INTERACTIONS IN LINGUISTICS, LITERARY & CULTURAL KNOWLEDGE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 28 September 2016 – The 4th International Conference on Linguistics, Literature and Culture (ICLLIC 2016) continues to discuss relevant topics and challenges facing education communities in developing countries in the SouthEast Asian region, as well as in other countries around the world.